Pemikiran Islam Tentang Jiwa Dalam Pemikiran Islam - Sri Nilawati; Mahmuddin; Andi Aderus (CBJIS: Cross-Border Journal of Islamic Studies, 2023)
Discussions about the soul (al-nafs) in the context of the Islamic world have begun since the emergence of Islamic thinkers in history. The soul is considered unimportant in Islamic teachings because the Koran states that the soul is God's business. This research adopts qualitative research methods with a focus on exploring Islamic thought regarding aspects of the soul in the context of Islamic thought. The library research approach is used as a data collection method, utilizing written works which include research results, publications and related literature that have a correlation with the research object. Research findings indicate that in the Qur'an, the word "al-nafs" (soul) is sometimes interpreted as spirit, indicating that the soul originates from the spirit. The spirit is considered the essence, while the soul is part of the spirit. Muslim philosophers contributed to understanding the soul, describing it as a spiritual substance with its own role and function. This journal also discusses the Koran's view of the soul, considering the role of ethics, morality, and the relationship between the soul and God in achieving soul perfection and eternal happiness in the afterlife.